ORGANIZATION AND MANAGEMENT OF THE INDEPENDENT WORK OF UNIVERSITY STUDENTS - Kenzhegulova С.Б.; Seidalieva Г.О.; Abdulkarimova Г.А.; Gusmanova Ф.Р. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
The article examines the main features of various forms and methods of organizing the independent work of university students. The opinion is substantiated that independent work, aimed at mastering the acquired knowledge and skills, allows students to fully understand the nature of the work performed and organize their own activities. In the context of the implementation of distance learning in higher education, the goals and functions of independent work of students have been revised, the role of which in the educational process is significantly increasing. In the course of the study to identify the importance of independent work of university students, results were obtained that allow one to draw some conclusions, for example, active independent work is possible only if there are motivating factors: student involvement in research activities, intensive pedagogy, individualization of tasks and the personality of the teacher